Investigating the 5P Model (Presage, Perception, Process, Pedagogy, Product) in Accounting Learning Process at Higher Education - Nurdian Susilowati; Lyna Latifah; Tusyanah Tusyanah (Jurnal Pendidikan dan Pengajaran, 2022)
Accounting learning needs to respond to current work needs that prioritize digital skills. But there are still many accounting students who do not fully understand about basic lessons in accounting. It was influenced by several factors. Therefore this study aims to analyse the relationship between gender, student perceptions of accounting learning, learning approaches, use of e-learning, and accounting learning outcome. This study use quantitative research with a correlational approach. The samples were 266 accounting students in the first year. The questionnaires were distributed online using the Google Forms platform. The independent t-test was used to allow researchers to test the hypothesis of comparing male and female students perceptions. Regression analysis is used to determine the relationship between variables. Based on the results, it was found that gender differences did not have a significant effect on student perceptions but showed a relationship between student perceptions, learning approaches, use of e-learning, and accounting learning outcomes. The use of a deep approach in learning will increase the role of e-learning, especially on the complexity of the material provided. In contrast, the ease of using e-learning can affect the understanding of accounting. The findings of this study provide the view that universities in Indonesia need to continue to develop the application of e-learning provided as learning media in pedagogical activities. This research has implications for accounting educators to design and implement educational programs that attract students to study accounting courses and develop their accounting skills.